2022
DOI: 10.3389/fimmu.2022.833715
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19/Tuberculosis Syndemic and Potential Antibody Therapy for TB Based on the Lessons Learnt From the Pandemic

Abstract: 2020 will be marked in history for the dreadful implications of the COVID-19 pandemic that shook the world globally. The pandemic has reshaped the normality of life and affected mankind in the aspects of mental and physical health, financial, economy, growth, and development. The focus shift to COVID-19 has indirectly impacted an existing air-borne disease, Tuberculosis. In addition to the decrease in TB diagnosis, the emergence of the TB/COVID-19 syndemic and its serious implications (possible reactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 179 publications
(188 reference statements)
0
7
0
1
Order By: Relevance
“…There is a lack of understanding of the immunopathological interplay of COVID-19 and TB syndemic, which leaves several unanswered questions on disease prognosis, clinical management, and determinants of mortality in TB-COVID-19 coinfection. [ 10 ] Studies have shown that TB might increase susceptibility to COVID-19 infection. [ 11 12 ] On the other hand, COVID-19 infection leads to significant reduction and functional exhaustion in total T cell counts, thereby increasing susceptibility to TB.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of understanding of the immunopathological interplay of COVID-19 and TB syndemic, which leaves several unanswered questions on disease prognosis, clinical management, and determinants of mortality in TB-COVID-19 coinfection. [ 10 ] Studies have shown that TB might increase susceptibility to COVID-19 infection. [ 11 12 ] On the other hand, COVID-19 infection leads to significant reduction and functional exhaustion in total T cell counts, thereby increasing susceptibility to TB.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Overall, TB-COVID-19 syndemia has several possible implications including reactivation of TBL after SARS-CoV-2 infection, TB-COVID-19 coinfection which consequently may lead to aggravation of an existing active TB condition, may increase the risk of severity of SARS-CoV-2 infection. 11,12 Understanding the nature of the interactions between MTB and SARS-CoV-2 pathogens will be crucial for the development of therapeutic strategies against coinfection.…”
Section: Morbidity and Mortality Risk Due To Tb-covid-19 Co-infectionmentioning
confidence: 99%
“…An important reason for refocusing on TB diagnosis during the pandemic is because of the emergence of the TB-COVID-19 syndemic. 11 It is unclear what the implications of this syndemia are; however, one possibility is that TB-COVID-19 coinfection will lead to a worsening of the existing active TB condition or an existing MTB infection may increase the risk of severity in SARS-CoV-2. 11,12 Another concerning aspect of this syndemic, is the reported cases of reactivation of latent TB in post-COVID-19 patients, 13 as one-quarter of the world's population is estimated to be affected by latent TB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a synergistic relationship between the spread of COVID-19 and pulmonary tuberculosis, which makes it more difficult to isolate the two diseases (Dass et al, 2022). COVID-19 is a new pandemic that causes terrible respiratory and enormous mental disease, ultimately resulting to lower quality of life in patients, whereas TB has been around for millennia and is responsible for the majority of fatalities in the globe (Cramer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%